2005
DOI: 10.1164/rccm.200407-981oc
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Src and Jak Kinases Protects against Lipopolysaccharide-induced Acute Lung Injury

Abstract: The cascade of cellular and molecular pathways mediating acute lung injury is complex and incompletely defined. Although the Src and Jak family of kinases is upregulated in LPS-induced murine lung injury, their role in the development of lung injury is unknown. Here we report that systemic inhibition of these kinases using specific small molecule inhibitors (PP2, SU6656, tyrphostin A1) significantly attenuated LPS-induced lung injury, as determined by histologic and capillary permeability assays. These inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
67
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(70 citation statements)
references
References 65 publications
2
67
1
Order By: Relevance
“…34 Our results revealed that mechanical ventilation induced the phosphorylation of Src both in lung tissue and isolated myofibroblasts, which can be suppressed by Src knockout or pharmacologic inhibition with PP2, a selective Src kinase inhibitor remaining effective up to 6 h after ALI. 14,20,22 However, PP2 is a hydrophobic chemical and can only be dissolved in the toxic organic solvent dimethyl sulfoxide. The recent development of nanoscale combinations of self-assembling peptides (EAK16-II) and amino acids can improve the biocompatibility of previous PP2 formulation and advance its potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…34 Our results revealed that mechanical ventilation induced the phosphorylation of Src both in lung tissue and isolated myofibroblasts, which can be suppressed by Src knockout or pharmacologic inhibition with PP2, a selective Src kinase inhibitor remaining effective up to 6 h after ALI. 14,20,22 However, PP2 is a hydrophobic chemical and can only be dissolved in the toxic organic solvent dimethyl sulfoxide. The recent development of nanoscale combinations of self-assembling peptides (EAK16-II) and amino acids can improve the biocompatibility of previous PP2 formulation and advance its potential clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its extensive use as a Srcselective inhibitor, recent studies have demonstrated that PP2 also reduced the activation of serine/threonine kinase/protein kinase B, beta-catenin, Jak kinase and phosphoinositide 3-OH kinase. 13,22 Further experiments are necessary to explore potential regulators of VILI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The kinetics of LPS-induced SFK activation in HMVEC-Ls parallel those described in LPStreated macrophages (30) and TNF␣-treated ECs (10). SFKselective inhibitors (PP2 and SU6656) attenuate both LPS-induced lung injury and increases in pulmonary vascular permeability in vivo (79). Other agonists, such as VEGF and TNF␣, also increase endothelial permeability through SFK activation (10,80).…”
Section: Discussionmentioning
confidence: 99%